The Jacobian conjecture: Approximate roots and intersection numbers - A. Guccione, Jorge; Guccione, Juan José; Horruitiner, Rodrigo; Valqui, Christian (Pontificia Universidad Católica del Perú, 2019)
En [14] Yansong Xu calcula el número de intersección de un par jacobiano usandos dos igualdades diferentes. Probamos la primera de estas desigualdades usando el lenguaje de [12], pero en lugar de la segunda solamente obtenemos una desigualdad.

We compute the intersection number of a Jacobian pair in two different ways following Yansong Xu, but using the language of [5]. We obtain nearly the same formulas, but with an inequality instead of an equality.
Keywords: Conjetura Jacobiana; https://purl.org/pe-repo/ocde/ford#1.01.00